Gibt es Präferenzen beim selbstgesteuerten Bewegungslernen? - Bund, A. (Messplätze, Messplatztraining, motorisches Lernen: ausgewählte Beiträge; 5. gemeinsames Symposium der dvs-Sektionen Biomechanik, Sportmotorik und Trainingswissenschaft; Universität Leipzig, Sportwissenschaftliche Fakultät, 19. bis 21. September 2002 / Veranst.: Sportwissenschaftliche Fakultät der Universität Leipzig ..., 2003)
In experiments concerning the learning of motor skills, participants were given the option to self-control some aspects of the practice situation, e.g. the frequen-cy of feedback (self-controlled learning). The results show that self-controlled learning enhances performance on a long-term basis. The aim of the present study was to examine wether learners prefer certain practice conditions for self-control, at first in a hypothetical practice situation. Participant`s task was to imagine that they had to learn the forehand topspin stroke in table tennis. The practice situation was described exactly. Then, participants indicated on a questionnaire which practice conditions they would prefer for self-control and which not. The results show that preferences regarding the self-control of practice conditions exist.